UV-Spectrophotometric Determination of Aceclofenac in Tablets - Saravanan, V.S.; L. Ware, Agasti; Gopal, N. (Asian Journal of Chemistry, 2010)
Simple, sensitive and economical UV-spectrophotometric method is developed for the estimation of aceclofenac in tablets. In this method, aceclofenac is determined accurately having absorbance maximum at 203 nm. Beer's law is obeyed in the concentration range 0-20 μg. Linearity is obtained in the concentration range of 2-10 μg/mL.